Ultrasound-Guided Thoracic Paravertebral Blockade: A Retrospective Study of the Incidence of Complications. Issue 5 (October 2016) - Pace, Meredith M.; Sharma, Balram; Anderson-Dam, John; Fleischmann, Katherine; Warren, Lisa; Stefanovich, Peter
Abstract : (Abstracted from Anesth Analg, 122:1186–1191, 2016) Thoracic paravertebral block (TPVB) produces ipsilateral somatic and sympathetic nerve blockade across several contiguous dermatomes and is known to effectively control acute postoperative pain. However, it is associated with serious potential complications, such as pneumothorax from pleural puncture and occasional local anesthetic toxicity.